The Prevalence and Impact of Heavy Menstrual Bleeding (Menorrhagia) in Elite and Non-Elite Athletes. - Georgie Bruinvels; Richard Burden; Nicola Brown; Toby Richards; Charles Pedlar (PLoS ONE)
To identify the prevalence and impact of heavy menstrual bleeding (HMB) in exercising females where anemia may have a significant effect on training and performance a 'Female Health Questionnaire' was designed incorporating a validated diagnostic HMB series, demographics, exercise ability data, training status, anemia, iron supplementation and whether the menstrual cycle had affected training and performance. The survey was conducted in two stages; initially online, advertised via social media, and then repeated via face-to-face interviews with runners registered for the 2015 London Marathon. 789 participants responded to the online survey, and 1073 completed the survey at the marathon. HMB was reported by half of those online (54%), and by more than a third of the marathon runners (36%). Surprisingly, HMB was also prevalent amongst elite athletes (37%). Overall, 32% of exercising females reported a history of anemia, and 50% had previously supplemented with iron. Only a minority (22%) had sought medical advice. HMB is highly prevalent in exercising females, associated with self-reported anemia, increased use of iron supplementation and a perceived negative impact on performance. Further research is needed to investigate the impact of HMB, iron deficiency and anemia in exercising females.